Risk-benefit analysis of surgical treatment strategies for cystic craniopharyngioma in children and adolescents - Schmutzer-Sondergeld, Michael; Quach, Stefanie; Niedermeyer, Sebastian; Teske, Nico; Ueberschaer, Moritz; Schichor, Christian; Kunz, Mathias; Thon, Niklas (Frontiers in Oncology, 2024)
Treatment strategies for craniopharyngiomas are still under debate particularly for the young population. We here present tumor control and functional outcome data after surgical treatment focusing on stereotactic and microsurgical procedures for cystic craniopharyngiomas in children and adolescents.From our prospective institutional database, we identified all consecutive patients less than 18 years of age who were surgically treated for newly-diagnosed cystic craniopharyngioma between 2000 and 2022. Treatment decisions in favor of stereotactic treatment (STX) or microsurgery were made interdisciplinary. STX included aspiration and/or implantation of an internal shunt catheter for permanent cyst drainage. Microsurgery aimed for safe maximal tumor resections. Study endpoints were time to tumor recurrence (TTR) and functional outcome including ophthalmological/ perimetric, endocrinological, and body-mass index (BMI) data.29 patients (median age 9.9 yrs, range 4-18 years) were analyzed. According to our interdisciplinary tumor board recommendation, 9 patients underwent stereotactic treatment, 10 patients microsurgical resection, and 10 patients the combination of both. Significant volume reduction was particularly achieved in the stereotactic (p=0.0019) and combined subgroups (p<0.001). Improvement of preoperative visual deficits was always achieved independent of the applied treatment modality. Microsurgery and the combinational treatment were associated with higher rates of postoperative endocrinological dysfunction (p<0.0001) including hypothalamic obesity (median BMI increase from 17.9kg/m 2 to 24.1kg/m 2 , p=0.019). Median follow-up for all patients was 93.9 months (range 3.2-321.5 months). Recurrent tumors were seen in 48.3% and particularly concerned patients after initial combination of surgery and STX (p=0.004). In here, TTR was 35.1±46.9 months. Additional radiation therapy was found indicated in 4 patients to achieve long-lasting tumor control.In children and adolescents suffering from predominantly cystic craniopharyngiomas, stereotactic and microsurgical procedures can improve clinical symptoms at low procedural risk. Microsurgery, however, bears a higher risk of postoperative endocrine dysfunction. A riskadapted surgical treatment concept may have to be applied repeatedly in order to achieve long-term tumor control even without additional irradiation.